Experience of using griseofulvin in the child below 1 year of age with tinea capitis. - Medvedeva, T.V.; Chilina, G.A.; Leina, L.M. (European Journal of Pediatric Dermatology, 2015)
A 4-month-old girl with tinea capitis caused by Microsporum canis was reported. The source of infection was not established. Taking into account the age of the patient, we decided to treat only topically the disease. The local treatment conducted for a month proved to be ineffective. Therefore, we decided with the pediatrician to use oral griseofulvin at a dose of 22 mg / kg per day. By the end of the first month of treatment with griseofulvin the clinical picture regressed.